2015
DOI: 10.1371/journal.pone.0141904
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenetic Tooth Reduction in Stenopterygius quadriscissus (Reptilia: Ichthyosauria): Negative Allometry, Changes in Growth Rate, and Early Senescence of the Dental Lamina

Abstract: We explore the functional, developmental, and evolutionary processes which are argued to produce tooth reduction in the extinct marine reptile Stenopterygius quadriscissus (Reptilia: Ichthyosauria). We analyze the relationship between mandible growth and tooth size, shape, and count, to establish an ontogenetic trend. The pattern in S. quadriscissus is consistent with hypotheses of tooth size reduction by neutral selection, and this unusual morphology (a functionally edentulous rostrum) was produced by a serie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 22 publications
2
24
0
Order By: Relevance
“…In S . quadriscissus , ontogenetic tooth reduction and tooth crown shape change increases the possibility of a concomitant niche shift (McGowan ; Dick & Maxwell ). If dental guild is correlated with diet (Massare ), such a change in shape implies a functional component: juvenile S. quadriscissus are best described as Pierce II Guild (Massare ), having relatively tall conical teeth with a sharp apex and no visible wear (Dick & Maxwell ).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In S . quadriscissus , ontogenetic tooth reduction and tooth crown shape change increases the possibility of a concomitant niche shift (McGowan ; Dick & Maxwell ). If dental guild is correlated with diet (Massare ), such a change in shape implies a functional component: juvenile S. quadriscissus are best described as Pierce II Guild (Massare ), having relatively tall conical teeth with a sharp apex and no visible wear (Dick & Maxwell ).…”
mentioning
confidence: 99%
“…quadriscissus , ontogenetic tooth reduction and tooth crown shape change increases the possibility of a concomitant niche shift (McGowan ; Dick & Maxwell ). If dental guild is correlated with diet (Massare ), such a change in shape implies a functional component: juvenile S. quadriscissus are best described as Pierce II Guild (Massare ), having relatively tall conical teeth with a sharp apex and no visible wear (Dick & Maxwell ). Conversely, adult S. quadriscissus possess teeth more accurately fitting the Smash guild (Massare ), having relatively short, robust teeth with a blunt apex, or are functionally edentulous, with teeth too small to have been erupted (Dick & Maxwell ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the dentition pattern of MUJA 4095 is consistent with that of Leptonectidae, particularly with MUJA 3687 and differs from that of Wahlisaurus massarae characterized by recurved crowns and large, bulbous infolded roots (Lomax, 2016). On the other hand, teeth of MUJA 4095 are inconsistent with tooth morphology of the other Lower Jurassic ichthyosaurs such as Temnodontosaurus, Ichthyosaurus and Stenopterygius, even considering ontogenetic change (Dick and Maxwell, 2015).…”
Section: Systematic Palaeontologymentioning
confidence: 68%
“…The taxonomic value of tooth morphology (size and shape) of Early Jurassic ichthyosaurs has been questioned. Recent contributions have shown that size and shape of teeth change during ontogeny, at least in Stenopterygius (Dick and Maxwell, 2015;Dick et al, 2016). In the case of Ichthyosaurus communis and I. intermedius, historically differentiated on the basis of tooth morphology, Massare and Lomax (2017) recognized different morphologies, although they pointed out that tooth features were not reliable to distinguish these two species.…”
Section: Systematic Palaeontologymentioning
confidence: 99%